2017
DOI: 10.1521/aeap.2017.29.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on HIV Testing Among WIC-Enrolled Postpartum Women: Implications for Intervention Development

Abstract: Low-income minority women are disproportionately represented among those living with HIV in the U.S and also at-risk for substance abuse and intimate partner violence – collectively called the SAVA syndemic which may impede HIV testing uptake. Views about HIV testing were assessed among women (ages 18–29) enrolled in a federally funded nutrition program for women, infants and children (WIC) in a large Mid-Atlantic city. A survey (n=80) and 3 focus groups were conducted in WIC offices located in neighborhoods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A number of the studies found that experiences of violence were associated with reduced HIV testing among women [30, 33, 34, 36, 39]. Qualitative studies described how fear of a violent reaction from one’s partner in the event of a positive test result contributed to reduced rates of HIV testing [43, 44]. A cross-sectional study by Turan et al (2011) supported these findings by demonstrating that anticipated stigma (defined as break-up of marriage/relationship and physical violence from a partner) upon testing positive for HIV was associated with refusing to test for HIV [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of the studies found that experiences of violence were associated with reduced HIV testing among women [30, 33, 34, 36, 39]. Qualitative studies described how fear of a violent reaction from one’s partner in the event of a positive test result contributed to reduced rates of HIV testing [43, 44]. A cross-sectional study by Turan et al (2011) supported these findings by demonstrating that anticipated stigma (defined as break-up of marriage/relationship and physical violence from a partner) upon testing positive for HIV was associated with refusing to test for HIV [27].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies found no significant relationship between experiences of violence and uptake of HIV testing among women [28, 29, 32, 41, 42, 44, 62]. Two of these studies utilized longitudinal designs.…”
Section: Resultsmentioning
confidence: 99%
“…A pointer to this complexity is the observed association between unknown HIV status and increased risk for sexual violence. Prior studies had demonstrated that sexual violence is associated with increased risk for HIV infection [53] and that gender-based violence impedes uptake of HIV testing [54] due to the fear of a violent reaction from one's partner in the event of a positive test [55,56]. These prior studies had associated physical violence with these highlighted risk [57][58][59] while the current study suggests that sexual violence may also reduce the likelihood of getting tested for HIV infection.…”
Section: Discussionmentioning
confidence: 55%
“…Because infrastructure and funding streams for various types of care are often siloed, novel care and reimbursement models may be needed to bridge the gap for patients and providers. Examples include implementation of HIV testing at Special Supplemental Nutrition Program for Women, Infants, and Children sites and family planning clinics [38][39][40] ; integration of preconception care into HIV care 14,41 ; and integration of perinatal HIV prevention into state syringe-access programs. 42 Although pregnant women with HIV are more likely to be linked to HIV care than nonpregnant women with HIV, linkage can be late or absent, 25 and some women may not receive recommended perinatal prevention interventions (eg, ART, scheduled cesarean delivery, intrapartum zidovudine) because of provider-or facility-related issues.…”
Section: Recommendation 5 Comprehensive Care For Women: Integrate Pementioning
confidence: 99%
“…Because infrastructure and funding streams for various types of care are often siloed, novel care and reimbursement models may be needed to bridge the gap for patients and providers. Examples include implementation of HIV testing at Special Supplemental Nutrition Program for Women, Infants, and Children sites and family planning clinics 38 -40 ; integration of preconception care into HIV care 14,41 ; and integration of perinatal HIV prevention into state syringe-access programs. 42…”
Section: Recommendations For Phscmentioning
confidence: 99%